Can We Find Stable Alternatives For Unstable Eclipse Interfaces? - Kawuma, Simon; Businge, John; Bainomugisha, Engineer (International Conference on Program Comprehension (ICPC), 2016)
The Eclipse framework is a popular and widely adopted framework that has been evolving for over a decade. Like many other evolving software systems, the Eclipse framework provides both stable and supported interfaces (APIs) and unstable, discouraged, and unsupported interfaces (non- APIs). However, despite being discouraged by Eclipse, the usage of bad interfaces is not uncommon. Our previous research has confirmed that a s Eclipse states, indeed A PIs are stable while non-APIs are unstable. Applications using non-APIs face compatibility challenges in new Eclipse releases. Furthermore, our previous studies further revealed that the reason why application developers use the unstable interfaces is because they cannot find s table interfaces w ith the functionality that they require. Moreover, in a study we conducted, Eclipse application developers stated that they manually find the functionality from Eclipse. Eclipse being a very large complex software system with a large number of committers, we hypothesize that as developers manually search for the functionality they require, it is possible that they miss stable interfaces offering the same functionality. To this end, using code clone detection techniques, we analyzed 18 major releases of Eclipse for possible clones. Our findings are three fold: (i ) we discover that indeed there exist clones in Eclipse, ii) we also discovered that some of the identified clones originate from different Eclipse projects, iii) our findings reveal that there is no significant number of APIs (less than 1%) offering the same or similar functionality as the non-APIs in all Eclipse releases we studied. This reveals that there are very few syntactic clones between API and non-API, thus developers were forced to either use non-API or find a n API that exists, that is similar in functionality, but not in syntax.
Keywords: Eclipse; Stable Interfaces; Unstable interfaces; Code clone; Evolution